Predictors of survival among HIV-positive children on ART in Swaziland. Issue 4 (2nd October 2017) - Shabangu, Patrick; Beke, Andy; Manda, Samuel; Mthethwa, Nobuhle
Abstract : The objective of the study was to determine predictors of survival among HIV-positive children (<15 years) in Swaziland. A retrospective cohort analysis of medical records for 4 167 children living with HIV who were initiated on antiretroviral therapy (ART) between 2004 and 2008, and followed up until 2014 was conducted in clinical settings at 36 health facilities. The Kaplan Meier Estimator, signed-ranks test, and the Cox proportional hazards regression model were applied to determine survival probabilities, significant difference among stratified survival functions and adjusted hazard ratios respectively. The results reveal that the median survival time for children was 78 months (95% CI: 77–79). Children who were initiated early on ART had higher survival probability over time (HR: 0.35 [95% CI: 0.21–0.57], p < 0.001) compared to those whose ART initiation was delayed. Children within the age group of <1 years had higher hazard (HR = 1.55 [95% CI: 1.16–2.08], p < 0.001) of death than children within the age group of 1–14 years. Children who were nourished had 88% lower hazard of death (HR: 0.12 [95% CI: 0.07–0.19], p < 0.001) than severely malnourished children. The study demonstrates that ART paediatric services are effective in increasing survival among HIV infected children and early initiated children have high survival probability. Active tuberculosis (TB), malnutrition, and delayed ART initiation remain predictors of poor survival among children living with HIV.